FSHR Trans-Activation and Oligomerization - Szymańska, Kamila; Kałafut, Joanna; Przybyszewska, Alicja; Paziewska, Beata; Adamczuk, Grzegorz; Kiełbus, Michał; Rivero-Müller, Adolfo (Frontiers in Endocrinology, 2018)
Follicle stimulating hormone (FSH) plays a key role in human reproduction through, among others, induction of spermatogenesis in men and production of oestrogen in women. The function FSH is performed upon binding to its cognate receptor - follicle-stimulating hormone receptor (FSHR) expressed on the surface of target cells (granulosa and Sertoli cells). FSHR belongs to the family of G protein-coupled receptors (GPCRs), a family of receptors distinguished by the diversity of signalling pathways they activate as well as the formation of cross-talking oligomers. Until recently, it was claimed that the FSHR occurred naturally as a monomer, however, the crystal structure as well as experimental evidence have shown that FSHR both self-associates and forms heterodimers with the luteinizing hormone/chorionic gonadotropin receptor – LHCGR. The tremendous gain of knowledge is also visible on the subject of receptor activation. It was once thought that activation occurs only as a result of ligand binding to a particular receptor, however there is mounting evidence of trans-activation as well as biased signalling among GPCRs. Herein, we describe the mechanisms of aforementioned phenomena as well as briefly describe important experiments that contributed to their better understanding